2017
DOI: 10.1007/s10811-017-1218-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects and antimicrobial activity of heterofucans from Sargassum filipendula

Abstract: Parasitic diseases are a human health problem mainly in low-income areas. The drugs available for the treatment of these diseases are far from satisfactory due to high costs, toxicity, and drug resistance. Sulfated polysaccharides are a complex group of bioactive polymers and can be obtained from seaweeds. The heterofucans from Sargassum filipendula (SF) present strong antiproliferative and antioxidant activities. However, their immunomodulatory and antimicrobial capacity have not been evaluated until now. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…It also acts as an intracellular messenger in the regulation of several physiological processes [ 30 ]. Therefore, the immunomodulatory activity of SPs extracted from seaweeds has been investigated by several authors, through the evaluation of NO levels produced by macrophages [ 4 , 14 , 31 ]. Therefore, in this study, NO levels were determined in RAW 264.7 macrophages exposed to different concentrations of the crude extract and polysaccharide fractions of C. cupressoides .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also acts as an intracellular messenger in the regulation of several physiological processes [ 30 ]. Therefore, the immunomodulatory activity of SPs extracted from seaweeds has been investigated by several authors, through the evaluation of NO levels produced by macrophages [ 4 , 14 , 31 ]. Therefore, in this study, NO levels were determined in RAW 264.7 macrophages exposed to different concentrations of the crude extract and polysaccharide fractions of C. cupressoides .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have observed different immunostimulatory activities of polysaccharides based on their degree of sulfation. In a study of SPs from Ulva rigida , Leiro et al [ 38 ] found that NO production was proportional to the amount of sulfate, whereas heterofucans obtained from Sargassum filipendula , with similar sugar/sulfate ratios, showed distinct NO production capacities [ 31 ]. The authors of this paper suggested that the position in which the sulfate groups are distributed in the molecule seems to be a factor more determining for immunostimulatory capacity than the degree of sulfation.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the results suggest that FUC is the agent responsible for the observed activation of macrophage-like cells. Actually, the immune modulatory activity of FUC has been already reported, and is mediated through the regulation of immune cells, including macrophages [49,50]. Although FUC has been shown to induce the production of TNF-α [11,48] and IL-8 [51] from macrophages and other immune cells [9], the polymer seems to be endowed with anti-inflammatory activity as well.…”
Section: Resultsmentioning
confidence: 99%
“…;Vatsos & Rebours 2015;Thanigaivel et al, 2016). For example, some algal genera with the broadest antimicrobial activities reported to date include Sargassum and Asparagopsis(Genovese et al 2012;Tanniou et al 2014;Marino et al 2016;Telles et al 2018). Previous studies have shown that Sargassum-enriched diets increased immune parameters and disease survival in Asian seabass (Lates calcarifer Bloch, 1790)(Yangthong et al 2016) and improved growth, immune parameters, hepatic antioxidant status and expression of immune-related genes in black sea bream (Acanthopagrus schlegelii Bleeker 1854)(Shi et al 2019), whilst Asparagopsis-enriched diet promoted batfish (Platax orbicularis Forsskal, 1775) growth and expression of immune-related genes…”
mentioning
confidence: 99%